Lithium Recovery Using Hydrogen Manganese Oxide Adsorbent Derived from Spinel Lithium Manganese Oxide : Pemulihan Litium Menggunakan Adsorben Hidrogen Mangan Oksida Berasal dari Spinel Litium Mangan Oksida - Widyabuningsih, Dewi; Hielwana, Hanadia; Pauti, Ekbar; Ridwan, Iwan; Rispiandi, Rispiandi; Eko Andrijanto (Fakultas Teknik, Universitas Brawijaya, 2023)
Lithium recovery from brine is recently attracting significant attention due to increasing industrial demand for energy storage, such as batteries. The lithium recovery from lithium brine was investigated using hydrogen manganese oxide adsorbent. The hydrogen manganese oxide adsorbent HMn2O4 (HMO) is derived from the spinel lithium manganese oxide (LMO), which is synthesized from LiOH and MnO2 precursor through the reflux method. The synthesized adsorbent was characterized using Scanning Electron Microscopy to identify its physical characteristics and its surface morphology. The adsorption capacity toward lithium solution was performed through an ion exchange process, and the adsorption values were determined using Atomic Absorption Spectroscopy (AAS). The synthesized HMO has a high lithium adsorption capacity for lithium-ion, which is 23 mg/g, and 10 mg/g for desorption. The optimum uptake capacity of HMn2O4 is 44% of the initial values (52 ppm) after 120 minutes of contact time. The synthesized hydrogen manganese oxide adsorbent has a potential industrial lithium recovery for large-scale application.